2012
DOI: 10.5539/ijms.v4n2p130
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Validating a Systematic Model of E-Advertising

Abstract: The paper's aim is that how the electronic system is able to transmit the message and is considered as an advertising tool, influencing factors on consumer's behavioral response should be identified in order to use this media desirably, effectively, and utilize the e-advertising advantages to satisfy consumers' needs. This is a research an applied research and a descriptive one with field studies. There are some casual relationships among the research variables. A questionnaire is used to collect data. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Allport (1935) describes an attitude as a state of mental readiness owing to experience, which exercises influence on a person's response to situations and objects in which they transpire. Attitudes are somewhat enduring and constant over time, which comprise of three components: cognitive, affective and behavioural (Hamidizadeh et al, 2012). This study is in agreement with Lutz (1985), who describes attitudes towards advertising (Aad) as a tendency to respond in a positive or negative way to a certain stimulus during exposure to communication.…”
Section: 3supporting
confidence: 90%
“…Allport (1935) describes an attitude as a state of mental readiness owing to experience, which exercises influence on a person's response to situations and objects in which they transpire. Attitudes are somewhat enduring and constant over time, which comprise of three components: cognitive, affective and behavioural (Hamidizadeh et al, 2012). This study is in agreement with Lutz (1985), who describes attitudes towards advertising (Aad) as a tendency to respond in a positive or negative way to a certain stimulus during exposure to communication.…”
Section: 3supporting
confidence: 90%
“…The nine-item scale that was used to measure intention-to-purchase was largely adapted from Putrevu and Lord (1994), Taylor and Hunter (2002) and Wu et al (2008), and was employed to measure this construct using a five-point Likert scale that ranged from strongly disagree to strongly agree. The nine-item scale that was used to assess purchase was mainly adapted from Martinez-Lopez et al (2005), Patwardhan and Ramaprasad (2005) and Hamidizadeh et al (2012) with a five-point Likert scale also being utilised. The last section of the questionnaire consisted of three multiple-choice questions on the demographic physiognomies that included gender, age and population group.…”
Section: Design Of Research Instrument and Data Collectionmentioning
confidence: 99%
“…The fourth important result of this study is that the cognitive, affective and behavioral effects of YouTube ads are positively associated with each other. Hamidizadeh, Yazdani, Tabriz, and Latifi (2012) indicated that cognitive response doesn't have a significant effect on the behavioral response. This result reinforces some previous research (e.g., Ahn & Back, 2017;Agapito, Valle & Mendes, 2013;Back & Parks, 2003;Hinson, Boateng, Renner & Kosiba, 2019;Matthes & Beyer, 2015;Punyatoya, 2019) that demonstrated the positive relationships among cognitive, affective and behavioral effects.…”
Section: Discussionmentioning
confidence: 99%
“…Various marketing communications studies have investigated the relationships among the communication effects (e.g., Ahn & Back, 2017;Agapito, Valle & Mendes, 2013;Back & Parks, 2003;Hamidizadeh, Yazdani, Tabriz, & Latifi, 2012;Hinson, Boateng, Renner & Kosiba, 2019;Matthes & Beyer, 2015;Punyatoya, 2019). Back and Parks (2003) found that cognitive brand loyalty influences on emotional brand loyalty, and emotional brand loyalty impacts on behavioral brand loyalty.…”
Section: H2 the Behavioral Intentions To Watch Youtube Ads Significantly Affect On Actual Engagement With These Adsmentioning
confidence: 99%
See 1 more Smart Citation